People of the Whirlpool : From The Experience Book of a Commuter's Wife - Wright, Mabel Osgood, 1859-1934 (Salt Lake City, UT : Project Gutenberg, 2004)
"People of the Whirlpool" by Mabel Osgood Wright is a novel written during the early 20th century. The story is narrated by Barbara, who reflects on her life as a mother of twins and the evolving social dynamics in her community as it comes into contact with wealthier outsiders from New York. It explores the theme of motherhood, familial relationships, and the contrasts between old and new societal values. The opening of the novel introduces Barbara in her attic, where she organizes her thoughts and memories about her children, Richard and Ian, who are lively twin boys. As she reminisces, she also considers the changes brought about by the arrival of affluent newcomers to her once-peaceful town, which she refers to as "the Whirlpool." Through her reflections and observations about parenting, her children's unique personalities, and her friendships$1 (Bparticularly with Lavinia Dorman$1 (BBarbara reveals her concerns about the social shifts and their implications for her family's traditional lifestyle. The narrative balances humor with introspective moments, setting the stage for deeper explorations of identity and community throughout the book. (This is an automatically generated summary.)s
Release date is 2004-03-01
E-text prepared by Kevin Handy, Dave Maddock, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Epistolary fiction; Diary fiction; United States -- Social life and customs -- 20th century -- Fiction